You will take care of me when I am old : norms on children’s caregiver obligations - an analysis with data from the European Values Study - Hess, Moritz [Verfasser]; Schmitz, Wiebke [Verfasser]; Naegele, Laura [Verfasser]; Stiemke, Philipp [Verfasser] (My University, 2023)
„Objective: We explore gender differences in support of the norm that children must provide care for their parents.Background:Society’s values and norms play a crucial role in deciding whether to provide family care. We investigate these values and norms on family care by analyzing which individual and country level factors affect them. Method: We use data from the European Values Study wave 5 and multilevel regression techniques. The question, “Adult children have the duty to provide long-term care for their parents”, serves as our dependent variable. The explanatory variables at the individual level are gender and further socio-demographic variables. At the country level, we include expenditures on health care, and the female labor force participation rate. Results: The results show that women, as well as those living in countries with high expenditure on health care and high female labor force participation rates, are less supportive of the norm that children have an obligation to provide care for their parents. Furthermore, the gender effect is stronger in countries with a higher female labor force participation rate.Conclusion: Norms and values on family care are not fixed and can change, as suggested by the differences between countries. They are also not shared by all social groups equally, as the differences between women and men and along other socio-demographics show.“ (Autorenreferat; BIBB-Doku)
Keywords: P 1.8 Ältere; G 2.4.5 Gender Mainstreaming; 370; 300; Alter Mensch; Eltern; Pflegebedürftigkeit; Betreuung; Pflege; Familienarbeit; Rollenerwartung; Werte; Geschlechtsspezifische Faktoren; Internationaler Vergleich